2017
DOI: 10.1111/mec.14448
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of Nautella italica R11 towards its macroalgal host uncovers new mechanisms of host–pathogen interaction

Abstract: Macroalgae (seaweeds) are essential for the functioning of temperate marine ecosystems, but there is increasing evidence to suggest that their survival is under threat from anthropogenic stressors and disease. Nautella italica R11 is recognized as an aetiological agent of bleaching disease in the red alga, Delisea pulchra. Yet, there is a lack of knowledge surrounding the molecular mechanisms involved in this model host-pathogen interaction. Here we report that mutations in the gene encoding for a LuxR-type qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Genus Nautella , identified in the umbrella of N. nomurai , was dominated by N. italica , an etiological agent of bleaching in the red alga Delisea pulchra ( Case et al, 2011 ; Gardiner et al, 2017 ; Hudson et al, 2018 ). The most abundant species of genus Acinetobacter , detected in the oral arms of C. nozakii , was A. schindleri , a human pathogen ( McGann et al, 2013 ; Jani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genus Nautella , identified in the umbrella of N. nomurai , was dominated by N. italica , an etiological agent of bleaching in the red alga Delisea pulchra ( Case et al, 2011 ; Gardiner et al, 2017 ; Hudson et al, 2018 ). The most abundant species of genus Acinetobacter , detected in the oral arms of C. nozakii , was A. schindleri , a human pathogen ( McGann et al, 2013 ; Jani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Schaffer et al have identified a plant metabolite, coumaric acid, that can replace the HSL tail to form a hybrid material-host signal [26], and so an analogous system with the HSL ring structure being host derived warrants further investigation. Alternatively, the Dunaliella teriolecta metabolite could be an HSL antagonist as Phaeobacter italicus R11 is known to produce HSLs which are antagonised by the algal metabolites, furanores [11] [27] [28].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of bacteriophage by plants is one means of plant defence against bacterial pathogens (Gill & Abedon, ). These results suggest Delisea may protect itself in the same way and that N. italica subverts this defence by repressing prophage, through a quorum‐sensing‐dependent mechanism (Hudson, Gardiner, Deshpande, & Egan, ).…”
Section: The Mechanisms Behind Influential Symbiosesmentioning
confidence: 95%